Revitalization Station Labuan, Medan with Post Modern Architectural Approach - Eddy, Firman; Simamora, Asep Didin (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Labuan Railway Station has been an integral part of the history of Indonesian railways since it began operating in the city of Medan for a significant period. Its existence has become an important marker in the cultural heritage of Medan, North Sumatra. Unfortunately, this station has now experienced a significant decline in operations and facilities, resulting in its current inability to operate fully. Therefore, a revitalization effort is necessary, focusing on providing new facilities without neglecting the preservation of the existing building's values. This study aims to evaluate the strategies required to redevelop the role of Labuan Station as a functional transportation hub while maintaining the historical integrity and authenticity of the building. Qualitative methods and a case study approach are used to analyze the challenges and opportunities associated with reviving the station's operations and redesigning its facilities. It is hoped that the results of this study will provide more comprehensive insights into how to enhance the function of railway stations with historical value. Consequently, this study can serve as a guide for stakeholders in redesigning Labuan Station without diminishing the historical values inherent in the station, as well as developing sustainable strategies for similar stations in Indonesia.